HUBUNGAN URUTAN KELAHIRAN ANAK DALAM KELUARGA DENGAN TINGKAT KEMANDIRIAN ADL (Activity Daily Living) PADA USIA (Pre-School) ANAK 4-6 TAHUN DI TK TUNASJAYA BANGSAL KABUPATEN MOJOKERTO - Rahmawati, Ima; Ilham Wicaksono, Akbar (JURNAL KEPERAWATAN BINA SEHAT, 2015)
Independence represent is individual attitude which obtained cumulatively during growth. Some factor influencing child independence in accomplishment of ADL (Activity Daily Living), one of them is birth sequence. According to Santrock, other factors which influence behavior of child independence is genetic (heredity), interest model or incompetition which parent fellow submit to child of everyday, influence model of friend coeval, influence of school, factor of social-economic, prosperity social factor, variation of culture. Research desain that used in this research is cross sectional type. Independence variable is sequence birth of child. Dependence variabel is ADL (Activity Daily Living) of child. Population in this research counted 50 child of Tunas Jaya kinderganten with their parents. Sampel according to criteria of inclution, sampling technique use sampling purposive. This research was done on 14 Mei until 17 Mei 2014. The collection file use primary file, and then calculated using Spearman Rho analysis file with α = 0,05. Result of research indicate that most birth sequence responder with first child counted 21 child ( 52,5%). Most independence responder of ADL (Activity Daily Living) with self-supporting category counted 25 child ( 62,5%). By using rank spearman rho test showing value where p < 0,05 Correlation Coefficient - 0,429 with Sig. ( 2-tailed) = 0.006 with correlation direction of negative, pursuant to result of examination with rank spearman rho test indicate that there are relation sequence birth of child with independence of ADL (Activity Daily Living) ) in TK Tunas Jaya Bangsal. Information about birth sequence and independence of ADL (Activity Daily Living) must be need good applying from parents to child so that can maximize child independence. The parents that very share in child independence, although level of birth sequence of child was different, child independence must be constructed early on for child growth later.Keyword : Sequence Birth, Independence of ADL (Activity Daily Living)